(untitled) (Bangladesh Journal of Zoology, 2020)
Study on bird species diversity, distribution and relative abundance is important for conservation efforts in local and national scale. However, bird diversity, distribution and relative abundance are little known in Karamjal Forest Station, Sundarbans. Ecological appraisal of bird species diversity, distribution and relative abundance of the avifauna of the Karamjal Forest Station were conducted from June 2015 to April 2016. A total of 156 bird species was recorded during the study period. Of which, one was globally Critically Endangered, Gyps bengalensis and two were Near Threatened i.e., Gyps himalayensis and Lusciniapectardens. The distribution of bird among habitat type was significantly different (f =22.069, p<0.05, df = 2). Walking trail was inhabited the highest species diversity (H’= 3.77) with the highest evenness (J=0.823) while water body was recorded the lowest species diversity (H’= 2.93) with the lowest evenness (J=0.804), it could have a relation to the availability of food items in the habitat. This study showed that despite huge tourist pressures this forest station harbour diverse avian species and thus this area should be managed in order to enhance the population of avian species. Bangladesh J. Zool. 48(1): 67-79, 2020